The Effect of Various Treatment of Bio Boost Fertilizer On The Growth and Yield of Melon (Cucumis melo. L) - Zulkarnain Sangadji; Nurul Fajeriana; Akhmad Ali (Faculty of Agriculture, Pattimura University, 2021)
Bio boost is a biological fertilizer containing superior soil microorganisms, useful for increasing soil fertility as a result of soil biochemical processes. Bio boost biofertilizer contains Azotobacter sp., Azospirillum sp., Bacillus sp., Pseudomonas sp., and Cytophaga sp. One of the applications of organic cultivation is the use of biological fertilizers in the cultivation of melons. Melon is a horticultural commodity that has a fairly high economic value and is profitable to be cultivated as a source of farmers' income. This research was conducted in Jamaimo Village, Mariat District, Sorong Regency from July to November 2020. This study used a single factor with a randomized block design consisting of 4 levels of treatment. Each treatment was repeated 4 times so that 16 experimental units were obtained. The concentration of Bio boost treatment is as follows: P1 = Treatment with a concentration of 500 ml bio boost + 1000 ml water; P2 = Treatment with a concentration of 700 ml bio boost + 800 ml water; P3 = Treatment with a concentration of 900 ml bio boost + 600 ml water; P4 = Treatment with a concentration of 1100 ml bio boost + 400 ml water. The results of the study found that the application of bioboost with various concentrations affected the length of the vine, the number of leaves, the weight of the fruit and the fruit diameter of the melon plant. Treatment with a concentration of 1100 ml bioboost + 400 ml water (P4) can increase the length of the tendrils up to 108.34 cm, the number of leaves 42.75, fruit weight 1.61 kg, and melon diameter 17.56 cm.Keywords: Organic_fertiliser; Bioboost; Melon